Correction: Depressive symptoms, HIV-related stigma and ART adherence among caregivers of children in vulnerable households in rural southern Malawi. - Kathryn L Spielman; Erica Soler-Hampejsek; Adamson S Muula; Lyson Tenthani; Paul C Hewett (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0247974.].